2014
DOI: 10.1186/1743-0003-11-73
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and functional variation in rat sciatic nerve following cuff electrode implantation

Abstract: BackgroundNerve cuff electrodes are commonly and successfully used for stimulating peripheral nerves. On the other hand, they occasionally induce functional and morphological changes following chronic implantation, for reasons not always clear. We hypothesize that restriction of nerve mobility due to cuff implantation may alter nerve conduction.MethodsWe quantified acute changes in nerve-muscle electrophysiology, using electromyography, and nerve kinematics in anesthetized Sprague Dawley rat sciatic nerves dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…It has been found that knee extension results in proximal displacement (Ellis ) and lengthening strains (Restaino et al. ) of the sciatic nerve in humans and rats, respectively. As the common peroneal nerve, which innervates TA, branches off the sciatic nerve posterior to the knee axis, also proximal displacement of this nerve with knee extension can be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that knee extension results in proximal displacement (Ellis ) and lengthening strains (Restaino et al. ) of the sciatic nerve in humans and rats, respectively. As the common peroneal nerve, which innervates TA, branches off the sciatic nerve posterior to the knee axis, also proximal displacement of this nerve with knee extension can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the net myofascial load cannot be explained by changes in the position of EDL relative to TA. It has been found that knee extension results in proximal displacement (Ellis 2012) and lengthening strains (Restaino et al 2014) of the sciatic nerve in humans and rats, respectively. As the common peroneal nerve, which innervates TA, branches off the sciatic nerve posterior to the knee ÂȘ 2015 The Authors.…”
Section: Comparison With Fe Model Of Skeletal Musclementioning
confidence: 99%
“…Because of the hard-to-change geometries, both traditional silicone rubber-based 3D cuff/helical electrodes with predefined stiff structures and PI-based electrodes with 2D planar structures have difficulties integrating with 3D peripheral nerves following surgical implantation. These drawbacks may induce irreversible damage to the nerves and cause serious biological issues, including inflammation, demyelination, axonal degradation, and blood vein compression (14)(15)(16)(17). Several adverse reactions caused by these drawbacks have been reported clinically, such as vomiting, cough, and difficulty in breathing in VNS therapy (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…(d) Schematic of implantation process: (left) the nanoclip is advanced towards an isolated nerve; (center) the nanoclip contacts the nerve resulting in elastic deformation of the trap doors and subsequent entry of the nerve into the central retention cavity; (right) as the nerve fills the cavity and makes contact with the electrode pads, the doors close behind the nerve to secure the nanoclip on the nerve. et al, 2008), which is comparable to the stiffness of peripheral tissues (Grill et al, 2009;Minev et al, 2015;Restaino et al, 2014) and correlates with a low immune response (Maiti et al, 2007;Salatino et al, 2017;Ward, 2008).…”
Section: Figure 1 | Thin-film-integrated Nanoclip Nerve Interface Ovementioning
confidence: 97%